Particulate composite protective coating using conventional melting approach - Maleque, Md Abdul; Nazrin, Idris; Rahman, Md Mustafizur; Hossain, Mohammad Sayeed
The particulate composite protective coating has been developed in thick surface layer on a low alloy steels by preplacing titanium carbide (TiC) ceramic particles into a shallow melt pool produced on a moving sample using conventional tungsten inert gas (TIG) torch melting approach. Protective coating ranging in thickness from 0.05 to 1.0 mm are formed, the thickness being determined by different heat input. The composite protective surface was investigated by a diversity of techniques, including scanning electron microscopy (SEM), energy-dispersive x-ray (EDX) and Microhardness tester. This article discusses the types of surface morphology or structures which have been produced by preplacing TiC particles on the substrate of low alloy steels and TIG melting/particle injection process (so called re-solidification process) and considers the effect on these structures developed by different heat input which in turn change the mode of dissolution. Special consideration is given to the degree of hardness development on the particulate composite protective surface after re-solidification via TIG torch melting technique.